(untitled) (Journal of Nepalese Business Studies, 2016)
This study investigates the impact of employment on marital stability of working men and women. The objectives of research were to identify the demographic and employment characteristics of spouses, to examine the relationship between spouse’s employment and marital stability and to analyze factors affecting marital stability. The study has employed descriptive as well as analytical research design. The study is based on primary data collected in Pokhara. The results of the study illustrates that there exits significant differences on mean scores of discuss on relatives, spend leisure, interaction with children, prepare family budget, intimate conversation and share information items by employment type. The results also indicate that in general the satisfaction from marital life is same across employment type but employment of spouse in government job leads to higher affection and commitment. In this connection the study mainly focuses on spouse’s employment and marital stability. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 102-115